Application of Radio Frequency Identification (RFID) Technology for Environment Improvement to Increase Efficiency of Spatial Perception and Accessibility for the Blinds - Tanapant, Samustpon (Journal of Architectural/Planning Research and Studies (JARS), 2022)
This paper describes an RFID-based system that helps localizing and navigating physical environmentsfor the visually impaired person. This responsive environment system was developed by using a complementarycombination of 1) Radio Frequency Identification (RFID) technology embedded in Braille Block and 2) along cane RFID-reader integrated with electronic compassion. The RFID tags store information of a braillepattern and give it to the reader to demonstrate information by sounds. There are 2 types of the informationdemonstrated: 1) the information that is automatically responsive with the location of hazards or obstacles2) the information that responds when the user pushes the button for asking the system to identify a physicalcondition of the environment, direction and destination. The results showed that the system increasedefficiency of spatial perception and accessibility for the visually impaired. The user was able to stop walkingbefore encountering with obstacles, recognize positions and directions of the walk way and access to thedestination correctly.